Effectiveness of Implementing the Village Financial System in Increasing the Accountability of Village Financial Reports - Ni Nengah Ari Widiantari; Ni Putu Yeni Yuliantari (Management and Applied Social Studies Review, 2023)
Purpose – This research activity aims to find out how effective the use of the Village Financial System (Siskeudes) is in increasing the accountability of village financial reports in Duda Timur Village, Selat District. Methodology –The technique or method used in this research activity is descriptive qualitative, consisting of data collection techniques through interviews, observation and documentation. Village officials starting from the village head, village secretary, and head of finance of Duda Timur Village became informants who were used as sources for this research activity. Findings – the results state that in Duda Timur Village the effectiveness of using the Village Financial System (Siskeudes) in increasing accountability in financial reports is based on appropriate terms, procedures and reporting stages, suitability of the information requested in the program or template, effectiveness feedback, as well as appropriate report forms. There are also several activity or activity options that do not appear in the application related to problems even though in the program or template there are problems with the indicators of suitability of the requested information. For this reason, the village government is required to report this matter to the district government and the problem has been handled properly.